Emergency Department Length of Stay and Its Association with Patient Outcomes - Khan, Zahid Ullah; Ullah, Khalil; Wahab, Abdul; Khan, Asif; Khan, Asif; Khan, Rustam (Journal of Neonatal Surgery, 2024)
Background: Prolonged emergency department length of stay (ED-LOS) has been linked to poor clinical outcomes as well as is one of the most important measurements of emergency department crowding. This relationship can be made clear to enhance patient safety and efficiency of care. Objective: The aim of the study was to assess the relationship of ED-LOS and patient outcome, including in-hospital mortality, ICU admission, hospital length of stay, and 7-day ED revisits, in a tertiary care hospital of Peshawar, Pakistan. Methods: The Emergency Department of Lady Reading Hospital between June 2023 and December 2023 was used to conduct a prospective observational study. Adults ( 18 and above) presenting to the ED were recruited. ED-LOS, demographic information, comorbidities, and triage desegregations were documented. The comparison of outcomes was carried out through descriptive statistics, chi-square tests, and multivariate logistic regression to identify free associations. Results: The median ED-LOS of 824 patients was 5.6 hours (IQR 3.29.4). Standard ED-LOS in excess of 8 hours was also significantly linked with in-hospital mortality (AOR 4.36), ICU admission (AOR 3.78), and 7-day ED revisits (AOR 2.89) (p < 0.001 all). Conclusion: Long ED-LOS is an important factor that predisposes poor outcomes. The efficient management of the patient flow, bed management, and identification of the time when care should be escalated can optimize patient safety and decrease avoidable morbidity.